Shu-Xie decoction alleviates oxidative stress and colon injury in acute sleep-deprived mice by suppressing p62/KEAP1/NRF2/HO1/NQO1 signaling - Wang, Mengyuan; Li, Bo; Liu, Yijiang; Zhang, Mengting; Huang, Caoxin; Cai, Teng; Jia, Yibing; Huang, Xiaoqing; Ke, Hongfei; Liu, Suhuan; Yang, Shuyu (Frontiers in Pharmacology, 2023)
Introduction: In humans and animal models, sleep deprivation (SD) is closely related with gastrointestinal diseases. Shu-Xie Decoction (SX) is a traditional Chinese medicine (TCM) with anti-nociceptive, anti-inflammatory, and antidepressant properties. SX is effective in the clinic for treating patients with abnormal sleep and/or gastrointestinal disorders, but the underlying mechanisms are not known. Therefore, this study investigated the mechanisms by which SX alleviates SD-induced colon injury in a mouse model. Methods: The mouse model of acute sleep deprivation (ASD) for 72 h was generated using the horizontal bar-style automated sleep deprivation system. ASD mice were untreated or treated with low-dose SX (SXL), high-dose SX (SXH), or S-zopiclone (S-z) as a positive control using the oral gavage. The body weights, fasting blood glucose (FBG) levels were measured for all the mice at different time points. After ASD modeling, the mice were sacrificed, and the blood and colons were harvested. The colon length was measured and the colon morphology was visualized using hematoxylin and eosin (H&E) staining. ROS levels were analyzed using the fluorescent ROS-sensitive probe, DCFDA/H2DCFDA. Spectrophotometry assays were performed to estimate the levels of redox biomarkers include reduced glutathione (GSH), malondialdehyde (MDA), and superoxide dismutase (SOD) activity. Quantitative real-time PCR (qRT-PCR) and western blotting assays were performed to detect the mRNA and protein expression levels of p62, KEAP1, NRF2, NQO1, and HO1. Results: ASD significantly increased FBG levels, decreased colon length, moderately increased the infiltration of inflammatory cells in the colon mucosa, altered the colon mucosal structure, increased the levels of ROS, GSH, MDA, and SOD activity compared with the controls. These adverse effects were significantly alleviated by SX treatment. ASD induced nuclear translocation of NRF2 in the colon mucosal cells and increased the expression levels of p62, NQO1, and HO1 transcripts and proteins, but these effects were reversed by SX treatment. Conclusion: SX decoction ameliorated acute sleep deprivation-induced oxidative stress and colon injury by suppressing the p62/KEAP1/NRF2/HO1/NQO1 signaling pathway.